Persepsi dan Perilaku Masyarakat terhadap Lembaga Keuangan Syariah: Perspektif Sosiologi dan Antropologi - Lidzikrirrofiqi, Muhammad Rifqi; Arifin, Tajul; Abdal, Abdal (CV. Strata Persada Academia, 2023)
This research analyzes how society views and behaves towards Islamic financial products from a sociological and anthropological perspective, which is a hot topic. The Sharia Finance Industry is at the core of the global financial map with the characteristics of Islamic moral and ethical principles. The author uses qualitative methods with in-depth interviews, participant observation, and content analysis of narratives of users of Islamic financial products used in this research's qualitative methodology with sociological and anthropological approaches. The results of this research highlight how social, cultural and religious factors shape people's perceptions and behavior towards Islamic financial products. In this context, the findings show that the level of religious understanding influences positive views towards Islamic finance. Apart from that, people's financial decisions are also influenced by economic stability, social influence from family, and recommendations from their social circle. Cultural factors and the social environment are also the main determinants in the adoption of sharia finance. The implications of this research include the importance of appropriate marketing and financial education that encourages a better understanding of sharia financial principles for the community.